Overview of Social Capital and Financial Cooperative through Bibliometric Visualizing from 1992-2022 - Iwang Suwangsih; Nanik Kustiningsih (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose : The purposes of this study to describe in the form of a map of research in the field of Social capital related to financial cooperative from international scale publications from the search engine Scopus. Design/methodology/approach: This study uses bibiometric and analyze search results provided by Scopus and by using Vosviewer software to show the keyword groups that can be identified from all relevant research in this study. Findings: There is very little research on social capital related to cooperatives, the results of the search for publications from 1992 to 2022 are only 175 documents. Originality/value: This paper is original Paper type: Research article